Síntese, caracterização e estudo eletroquímico de radicais orgânicos do tipo nitronil nitróxido substituído com tiofenos com potenciais aplicações em células solares - Matheus Henrique Ignácio Souto (2024)
This work addresses the synthesis and characterization of nitronyl nitroxide radicals (NTIR) substituted with different thiophenes. NTIR are already applied in the construction of molecular magnets and as free radical scavenging agents, while thiophenes are aromatic compounds with interesting properties, being used to obtain semiconductor materials. Therefore, studies on the association of these two materials may allow obtaining organic semiconductor materials with good efficiencies for applications in solar cells. The synthesis was carried out from the reaction of 2,3-bis(hydroxylamino)-2,3-dimethylbutane with thiophene aldehydes, obtaining yields between 30,0 - 50,0%, depending on the thiophene used. The products were characterized and their physical, electronic and optical properties were obtained. The optoelectronic characterization was carried out by obtaining the optical and electronic band gaps from the results obtained via ultraviolet and visible spectroscopy and cyclic voltammetry, respectively. Furthermore, in order to improve the electronic characteristics, an electrochemical study of the polymerization of the formed radicals and their precursors was carried out, evaluating different parameters and determining the conditions under which the process occurs more easily. The study made it possible to observe which parameters can be modulated in order to reduce the potentials required for the electropolymerization of NTIR substituted with thiophenes.